MATERNAL ROLE CONFIDENCE: CONCEPT PAPER - Mugadza, Gladys; Longwe, Rachael; Njanje, Agness; Zvinavashe, Mathilda; Haruzivishe, Clara; Rukweza, Judith (IJRDO- Journal of Educational Research, 2017)
The purpose of this concept paper was to determine a concept analysis on Maternal Role Confidence of during the early postpartum period. A concept analysis using Walker &Avanti was done. Eight articles were systematically reviewed to define and clarify maternal role confidence. The following search engines were used as data sources: google scholar, PubMed, Biomed central and www.opendoar.org. Attributes of maternal role confidence include the following, maternal intrinsic role, ask for help, and identifying baby cues. The attributes were identified to standardize care. Despite the dynamic nature of maternal role confidence, the provided definition of maternal role confidence facilitate a clearer understanding of what maternal role confidence is.